1991
DOI: 10.1021/bp00012a008
|View full text |Cite
|
Sign up to set email alerts
|

Filtration Properties of Mycelial Microbial Broths

Abstract: The filtration properties of three mycelial cultures (Streptomyces griseus, Streptomyces tendae, and Penicillium chrysogenum) have been measured and quantified in terms of standard filtration equations. Three of the filtration parameters, the hyphal density, the index of compressibility, and the Kozeny constant, were found to vary systematically with broth age and with the visually observed morphology (i.e., pellets VI filaments). Since broth age and mycelial morphology both have a strong influence on bioreact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
3
11
0
Order By: Relevance
“…In related studies, Oolman and Liu [7] and Liu and Yu [39] have shown that the compressibility index (n) increased when the cell morphology changed from predominantly filaments to predominantly pellets. Interestingly, they found a good correlation between cake compressibility and Kozeny constant, whereby increasing Kozeny constant was associated with increasing cake compressibility.…”
Section: Relating Cake Compressibility To Cell Morphologymentioning
confidence: 96%
See 2 more Smart Citations
“…In related studies, Oolman and Liu [7] and Liu and Yu [39] have shown that the compressibility index (n) increased when the cell morphology changed from predominantly filaments to predominantly pellets. Interestingly, they found a good correlation between cake compressibility and Kozeny constant, whereby increasing Kozeny constant was associated with increasing cake compressibility.…”
Section: Relating Cake Compressibility To Cell Morphologymentioning
confidence: 96%
“…An alternative approach was used by Shimuzu et al [6] who measured the dry cell concentration and assumed that the moisture content of a typical cell is 70 wt%. Oolman and Liu [7] devised a technique in which interstitial water of a wet filter cake was replaced by ethanol which was subsequently evaporated to leave pure biomass that was then weighed to yield the wet cell mass. Okamato et al [8] measured the wet cell concentration by filtering a known volume of suspension and leaving the deposited cake exposed to pressurised nitrogen overnight.…”
Section: A Note On the Measurement Of Wet Cell Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The equations used to correlate specific resistance data are varied but most authors use the classic power-law equation [3], [4] and [5] or, in some cases (especially for microbial suspensions), a linear relationship between specific resistance and pressure is employed [6], [7] and [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous workers have examined such process interactions. Changes in the morphology of P. chrysogenum that occur during fermentation have been shown to result in very different filtration rates being achieved in subsequent downstream processing [27] while the conditions of bead milling S. cerevisiae impact the efficiency of subsequent depth filtration [24]. Here a clear compromise between the extent of milling to achieve good product release and the consequent blockage of the filter medium by fines was apparent.…”
Section: Introductionmentioning
confidence: 99%